Between an Italian Restaurant and a Polish Factory. "Oksana" by Włodzimierz Odojewski as a Prefiguration of Polish-Ukrainian Discussions after 2014 - Kupidura, Ryszard (Porównania, 2024)
In the article, the author returns to Włodzimierz Odojewki’s "Oksana", first published twenty five years ago, and analyzes how it fits into the contemporary context of the Polish-Ukrainian dialogue. As Inga Iwasiów observes, the prosaic-designed model of encounter turns out to be interesting in the context of the running experience, when Poles and Ukrainians increasingly share space without special occasion while remaining dependent on the influences of memory politics. To draw comparisons, the author references a range of contemporary artistic expressions in the article, including theatrical, literary, and cinematic works.